PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN MATAHARI DEPARTEMENT STORE JEMBER - Nely Supeni (STIE Mandala Jember, 2012)
Consumer is the most important thing that needs to be considered by a company. Consumers will remain loyal to the company if they feel satisfied with the product and servise provided by the company. Matahari Departement Store is one of the departement store in Jember wich has a loyal customer to them. This study was to determine the effect of product quality and servise quality on customer loyalty Matahari Departement Store. The data used is primary data wich one type of data based on its source which usually obtained by field survei using all the original data collection methods. The type of data in this study are ordinal data. The sample used as many as 60 respondents. The analytical tool used is multiple linear regression with a significance level of 5% or 95% confidence internal. Regression results show that partially X1 (product quality) is significant. X2 (quality product) is significant too. Simultaneously indicates that all independent variabels (quality products and quality service) effect simultaneously on customer loyality. R square 0,785 wich means that 78,5% change of customer loyality caused by the product quality and service quality.